2018
DOI: 10.3889/oamjms.2018.308
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of CAD/CAM versus Conventional Complete Dentures - A Review

Abstract: BACKGROUND:The introduction and evolution of CAD/CAM technology into complete dentures fabrication brought high expectations in improving disadvantages associated with conventional methods.AIM:The purpose of this review was to analyse the existing literature on computer-engineered complete dentures and to determine their advantages over the conventional dentures.MATERIAL AND METHODS:An electronic search of the English literature from January 1994 to March 2018 was performed in PubMed/MEDLINE, using the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
76
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 21 publications
1
76
0
7
Order By: Relevance
“…Consequently, there is a more extensive literature base available for milled complete dentures as compared to 3D printed complete dentures. Although the technology is relatively new, there is growing evidence that the clinical outcomes of digitally fabricated dentures trend toward favorable ‐ particularly for milled dentures 11–15 . Digitally fabricated dentures generated by milling are typically milled from a puck of poly(methylmethacrylate) (PMMA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there is a more extensive literature base available for milled complete dentures as compared to 3D printed complete dentures. Although the technology is relatively new, there is growing evidence that the clinical outcomes of digitally fabricated dentures trend toward favorable ‐ particularly for milled dentures 11–15 . Digitally fabricated dentures generated by milling are typically milled from a puck of poly(methylmethacrylate) (PMMA).…”
mentioning
confidence: 99%
“…This has been studied with milled dentures showing as good 17 or improved 18–22 fit/retention than conventional processing (press pack, pour and injection methods). Other studies have shown dentures fabricated by milling have improved tensile strength and fracture toughness 12,16 . These properties are further improved with a monolithic puck, where the teeth and denture base are milled out of the same material, from a single puck (Avadent, AZ; Ivoclar, NY).…”
mentioning
confidence: 99%
“…Auf der Basis der vorliegenden In-vitro-Studien bietet die digitale Fertigung von Totalprothesen durch die Nutzung industriell präfabrizierter Materialien werkstoffkundliche Vorteile hinsichtlich der mechanischen Eigenschaften und ermöglicht eine verbesserte Passung [1]. Insbesondere durch die Verbesserung der mechanischen Eigenschaften erscheint eine Reduktion des Frakturrisikos möglich.…”
Section: Diskussionunclassified
“…Wie erste Untersuchungen zur Zeit-und Kosteneffizienz belegen, eröffnet die digitale Fertigung von Prothesen ein signifikantes Potenzial für Zeit-und Kostenersparnisse in Praxis und Labor [24]. Dieser Aspekt ist neben den dargelegten qualitätsverbessernden Aspekten ein wichtiger Punkt für die zukünftige Bedeutung des digitalen Workflows im Bereich der abnehmbaren Prothetik [1,7].…”
Section: Diskussionunclassified
See 1 more Smart Citation